Cognitive droughts - Guilherme Lichand; Anandi Mani (University of Zurich, Department of Economics, 2020)
Poverty involves both low income levels and high income uncertainty. Do both these dimensions of being poor capture attention in ways that distort decision-making and trap people in poverty? We examine these issues using real-life shocks faced by farmers in Brazil: random payday variation affecting income levels, and rainfall shocks that affect income uncertainty. We find that it is income uncertainty that systematically has adverse cognitive effects; low income levels affect only the poorest households. The net adverse impacts on cognitive function prevail even though both dimensions of poverty reallocate attention to scarce-resource tasks. These results broaden our understanding of the impacts of uncertainty by exploring a psychological channel distinct from risk aversion, and help reconcile apparently contradictory evidence on the cognitive impact of poverty in previous studies.
Keywords: D81; D91; I32; 330; uncertainty; attention; psychology of poverty; scarcity